Comparative study of aerodynamic characteristics of various sail type wind turbines - Kussaiynov, K.; Sakipova, S.E.; Kambarova, Zh.T.; Alkenova, A.M. (Publishing House of the KarSU named after E.A.Buketov, 2015)
The article presents the results of experiments on the study of aerodynamic characteristics of various models of sail-type wind turbines under different flow conditions. The description of procedure of testing and measurement of aerodynamic forces is presented. The authors obtained thrust and drag forces graphs at different rates and angles of attack of the air flow. They defined the dependence of head drag and thrust forces coefficients when Reynolds number changed. The results of the comparative analysis of the aerodynamic characteristics of three models of sail-type wind turbine are presented.
Keywords: aerodynamics; sail type wind turbine; drag force; traction force; angle of attack